2021
DOI: 10.1097/md.0000000000024056
|View full text |Cite
|
Sign up to set email alerts
|

Associations between adolescents’ earphone usage in noisy environments, hearing loss, and self-reported hearing problems in a nationally representative sample of South Korean middle and high school students

Abstract: Few epidemiological studies have examined the relationship between earphone usage and hearing loss in adolescents. This study identified the prevalence of hearing loss in South Korean adolescents using representative national survey data and evaluated the relationship between earphone usage in a noisy environment and hearing loss. This study analyzed 532 subjects (12–19 years) who participated in a 2012 national survey and completed health and noise environment exposure questionnaires and pure tone audiometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 30 publications
1
12
0
5
Order By: Relevance
“…The vestibular inefficiency noted by Singh and Sasidharan may be one reason for the incidence of vertigo reported by regular PMS users in our study. The reduction we saw in hearing sensitivity among regular PMS users accords with previous reports [1,7,11]. Similarly, temporary threshold shift, which is an early indicator of permanent damage to hearing and an early sign of noise-induced hearing loss, has also been reported [1,7].…”
Section: Groupsupporting
confidence: 91%
See 2 more Smart Citations
“…The vestibular inefficiency noted by Singh and Sasidharan may be one reason for the incidence of vertigo reported by regular PMS users in our study. The reduction we saw in hearing sensitivity among regular PMS users accords with previous reports [1,7,11]. Similarly, temporary threshold shift, which is an early indicator of permanent damage to hearing and an early sign of noise-induced hearing loss, has also been reported [1,7].…”
Section: Groupsupporting
confidence: 91%
“…Because music, as with other noises, has been reported to be harmful to the auditory system unless within safe limits, we felt it would be worthwhile to study the music listening behaviors of young adults. Previous studies have reported prolonged and unsafe music listening behaviors in this group [1,3,11]. A few studies in the literature have reported reduced hearing and vestibular dysfunction exhibited by individuals who use PMS regularly [1,3].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In South Korea, Byeon (2021) explored the prevalence of hearing loss in adolescents based on the data from the 2013 Korea National Health and Nutrition Examination Survey [ 10 ]. The results revealed a 22.6% hearing-loss prevalence in adolescents who used earphones in a noisy environment.…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies [ 13 , 14 ] have used machine learning based on big data to identify the risk factors of a disease while considering multiple risk factors. However, employing a single machine learning technique may show lower prediction performance, depending on the used algorithm, and it is possible to induce errors because the bias existing in each algorithm can affect the prediction result.…”
Section: Introductionmentioning
confidence: 99%